Pharmacokinetic Study of Icariside II After a Single Dose Administration of YiGu Capsule in Healthy Chinese Volunteers - Liu, X.-y.; Wei, C.-m.; Zhang, R.; Yuan, G.-y.; Guo, R.-c. (Drug Research, 2013)
To investigate the pharmacokinetic characteristics of icariside II after a single oral dose administration of YiGu Capsule in healthy Chinese volunteers. 8 (4 female) healthy Chinese volunteers were involved and administrated for 15 doses of YiGu Capsule after fasting overnight. 4 ml of blood samples were collected at scheduled time before and after administration. Icariside II in human plasma was separated on a Agela Venusil XBP-C18 column (250 mm×4.6 mm, 5 μm), and eluted using acetonitrile-water (containing 0.1% formic acid) (70:30, V/V) as mobile phase. The analytes were detected with a triple quad HPLC-MS/MS using ESI with positive ionization. Ions monitored in the multiple reaction monitoring mode were m/z 515.1 (precursor ion) to m/z 369.1 (product ion) for icariside II and m/z 321.0 (precursor ion) to m/z 275.0 (product ion) for lorazepam (internal standard).The plasma concentration of icariside II was determined by established HPLC-MS/MS method after disposition and its pharmacokinetic parameters were analyzed and evaluated by PK Solver Software (version 1.0). The Cmax, Tmax, t1/2, AUC0–24, AUC0−∞, MRT0−∞−1, 2.50±1.91 h, 7.61±2.81 h, 12.68±4.86 ng · mL−1 · h, 14.22±5.75 ng · mL−1 · h, 9.55±1.56 h, 12.81±7.94 L · h−1 and 121.70±32.70 L. The established HPLC-MS/MS method was sensitive, selective and rapid for icariside II pharmacokinetic study.
Keywords: icariside II; LC-MS/MS; pharmacokinetics; human plasma